Optical Absorption Measurements of Hydrogen Chloride at High Temperature and High Concentration in the Presence of Water Using a Tunable Diode Laser System for Application in Pyrohydrolysis Non-Ferrous Industrial Process Control. Issue 6 (June 2015) - Tzanetakis, Tommy; Susilo, Robin; Wang, Zhenyou; Padmanabhan, Arathi; Davis, Boyd R.; Thomson, Murray J.
A tunable diode laser (TDL) was used to measure hydrogen chloride (HCl) spectra at 5747 cm −1 (1.74 μm) and temperatures of 25–950 °C in a quartz cell. The purpose was to evaluate the capability of monitoring HCl concentration under pyrohydrolysis conditions using a near-infrared (NIR) laser. These conditions are characterized by 20–40% HCl, 2–40% H2 O, and the presence of metal chloride vapors at temperatures of 600–1000 °C. Spectral peak area measurements of HCl–N2 mixtures at atmospheric pressure and a path length of 8.1 cm showed linear absorption behavior between concentrations of 5–95% and temperatures of 25–950 °C. Results from the addition of 2–40% water (H2 O) indicate that the HCl peak area relationships are not affected for temperatures of 350–950 °C. Evaporating NiCl2 within the cell did not show spectral interference effects with HCl between 650 and 850 °C. The results from this work indicate that a near-infrared optical sensor is capable of measuring high HCl concentrations at high temperatures in the presence of high H2 O content during pyrohydrolysis process conditions.